1988
DOI: 10.1136/bmj.297.6660.1371
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory pH monitoring of gastro-oesophageal reflux in "morning dipper" asthmatics.

Abstract: premature peripheral vascular disease-that necessitated a hospital stay of more than 30 days they took nearly as long as the elderly (aged 70 and over) to recover sufficiently to leave hospital (mean 50 5 days v 57 3 days). ConclusionsIf efficiency in a surgical service means a high throughput of patients and a low rate of cancellation we have three suggestions.(1) A surgical service might be provided with fewer beds if patients for elective operations were always admitted on the day of operation and discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
1
4

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 11 publications
(3 reference statements)
2
31
1
4
Order By: Relevance
“…These results are in contrast to those of some studies [9][10][11][12][13], but are comparable with those of others [14,15]. The failure to show any benefit in studies has been ascribed to several factors, including insufficient inhibition of acid reflux and the short duration of the study treatment.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…These results are in contrast to those of some studies [9][10][11][12][13], but are comparable with those of others [14,15]. The failure to show any benefit in studies has been ascribed to several factors, including insufficient inhibition of acid reflux and the short duration of the study treatment.…”
Section: Discussioncontrasting
confidence: 56%
“…Some studies have indicated that pulmonary symptoms and lung function can be improved by intensive treatment of acid reflux, both by surgery and medical treatment [9][10][11][12][13]; however this has not been confirmed in other studies [14,15]. The discrepancy between outcomes may result from the fact that these studies did not consider airway hyperresponsiveness as an inclusion criterion or an end parameter.…”
mentioning
confidence: 42%
“…GERD is more prevalent in asthmatics compared with control populations and asthmatics frequently associate GERD symptoms with their asthma symptoms. Previous studies have estimated the prevalence of GERD in adult asthmatics at between 34% and 80% [8][9][10] . Asthma symptoms also correlated with esophageal pH events on 24-h esophageal pH monitoring [11] .…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies dealing with asthma outcome and medical anti-reflux therapy. Field and Sutherland (1998) reviewed the previously published data on medical anti-reflux therapy with H 2 -receptor blockers (H 2 blockers), cimetidine (Goodall et al 1981;Larrain et al 1991) and ranitidine (Harper et al 1987;Nagel et al 1988;Ekstrom et al 1989;Gustaffson et al 1992), and with a proton pump inhibitor (PPI) omeprazole (Ford et al 1994;Meier et al 1994;Harding et al 1996;Teichtahl et al 1996), showing that asthma symptoms were improved. Kiljander (2003) suggested that, in the management of GERD-related asthma, PPIs other than omeprazole should be used at double the standard dose.…”
mentioning
confidence: 99%